2022
DOI: 10.1371/journal.pone.0274862
|View full text |Cite
|
Sign up to set email alerts
|

Women with perinatal suicidal ideation–A scoping review of the biopsychosocial risk factors to inform health service provision and research

Abstract: Objectives This review aims to map the existing evidence on perinatal suicidal ideation, identify biopsychosocial risk factors associated with suicidal ideation and make recommendations for service provision and future research. Methods Scoping review guided by Arskey’s and O’Malley’s (2005) framework. Five academic databases (PsycINFO, MEDLINE, CINAHL, ASSIA and Academic Search Complete) were searched from 1st January 2009 to 1st April 2022. Studies were screened by title, abstract and full text against inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…These studies also suggest that the relationship between neuroticism and depression may be even more significant during pregnancy and after childbirth, two periods particularly impacting on woman's health from a hormonal and emotional point of view [46]. A recent systematic review and meta-analysis indicated that higher levels of neuroticism were associated with an increased risk of postpartum depression [21] and suicidal ideation in the perinatal period [47,48]. Our study aimed to test these associations in a large real-world setting, even if the risk of suicide was clinically detected but not measured in a standardized manner.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These studies also suggest that the relationship between neuroticism and depression may be even more significant during pregnancy and after childbirth, two periods particularly impacting on woman's health from a hormonal and emotional point of view [46]. A recent systematic review and meta-analysis indicated that higher levels of neuroticism were associated with an increased risk of postpartum depression [21] and suicidal ideation in the perinatal period [47,48]. Our study aimed to test these associations in a large real-world setting, even if the risk of suicide was clinically detected but not measured in a standardized manner.…”
Section: Discussionmentioning
confidence: 96%
“…Some authors have suggested considering individual levels of neuroticism in order to estimate the risk of developing emotional or mood disorders (higher levels are associated with higher risk), whereas some others have suggested that neuroticism may be a specific, identifiable pattern in patients suffering from mood disorders [5,6]. Bright et al [21] also reported that higher levels of neuroticism could predict suicidal ideation among women during the perinatal period. In addition, neuroticism was significantly associated with low perceived social support during pregnancy as well as poor adjustment after childbirth [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The initial psychopathological impact on our sample also included some level of suicide ideation in three subjects. Several previous reviews include perinatal loss among the risk factors for suicide ideation or suicide attempts in the perinatal period [36][37][38][39]. In their scoping review of the biopsychosocial risk factors for perinatal suicidal ideation, Bright, Doody and Tuohy [36] identified traumatic experiences relating to miscarriage and pregnancy loss as an independent risk factor for suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the biopsychosocial risk factors for perinatal suicidal ideation are varied and complex and may need to be explored in a cultural and social context. 19 Hence, there is a need for further qualitative and quantitative research to be done among females experiencing perinatal suicidal ideation to get a deeper understanding of their experiences. There is also a need for further research to identify protective factors for perinatal suicidal ideation.…”
Section: Variablesmentioning
confidence: 99%